2006
DOI: 10.1111/j.0014-3820.2006.tb01215.x
|View full text |Cite
|
Sign up to set email alerts
|

Within-Host Competition in Genetically Diverse Malaria Infections: Parasite Virulence and Competitive Success

Abstract: Abstract. Humans and animals often become coinfected with pathogen strains that differ in virulence. The ensuing interaction between these strains can, in theory, be a major determinant of the direction of selection on virulence genes in pathogen populations. Many mathematical analyses of this assume that virulent pathogen lineages have a competitive advantage within coinfected hosts and thus predict that pathogens will evolve to become more virulent where genetically diverse infections are common. Although th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
181
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(192 citation statements)
references
References 72 publications
6
181
5
Order By: Relevance
“…Similarly, results of earlier studies on within-host competition showed fitness disadvantages for lesser virulent parasites (Gower and Webster 2005; Bell et al. 2006). The disadvantage is explained by competition favouring increased host exploitation and thus increased virulence (Choisy and de Roode 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, results of earlier studies on within-host competition showed fitness disadvantages for lesser virulent parasites (Gower and Webster 2005; Bell et al. 2006). The disadvantage is explained by competition favouring increased host exploitation and thus increased virulence (Choisy and de Roode 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This competition is for resources or enemy-free space (Read and Taylor 2001;Råberg et al 2006;. Competitive ability in this experimental system is correlated with virulence (de Roode et al 2005a(de Roode et al , 2005bBell et al 2006). In CD4 ϩ T cell-depleted mice, competition between rodent malaria parasites is enhanced ), in part due to resource limitation (Hellriegel 1992;Hetzel and Anderson 1996;Haydon et al 2003;Mideo et al 2008).…”
Section: Introductionmentioning
confidence: 94%
“…One of the most useful attributes of P. chabaudi is the variety of well-characterized cloned lines (Box 1) [3]. These lines are all synchronous (unlike P. berghei ANKA or P. yoelii [4]) and exhibit a spectrum of disease severity [5], different levels of sequestration [6] and transmissibility to mosquitoes [7]. The most commonly used line is P. chabaudi chabaudi (AS), which is generally non-lethal, similar to malaria caused by both P. vivax and P. falciparum in humans (less than 0.5% lethality), but sequesters (adheres) on vascular endothelium, induces a chronic infection [8], and can be relatively easily transmitted through Anopheles stephensi mosquitoes.…”
Section: The Rodent Malarias: From the Gallery Forest To The Labmentioning
confidence: 99%